Texts and Contexts— Into Pedagogy of Social Sciences in Primary Classes - Bassi, Tripti (THE PRIMARY TEACHER, 2018)
Social Sciences occupy unique significance in the disciplinary domain of schoolknowledge. They are integral for building understanding of social realities andmeanings. In the form of Social Studies, they enrich school learning by introducingchildren to concepts related to the self, neighbourhood and society, among others.This paper is based on content analysis of three textbooks of Social Studiesintroduced by the State Council of Educational Research and Training, Delhi,in 2004, following a distinct approach by introducing children to concepts ina sequential and developmental manner through Class III textbook ‘My Delhi’(Meri Dilli), Class IV textbook ‘Our India’ (Hamara Bharat), and ‘Our World’(Hamari Duniya). According to the National Curriculum Framework 2005, ClassIII onwards Environmental Studies should be introduced for building cognitivecapabilities. Discussions related to natural and social environments have to bepresented to the learners in an integrated and cohesive manner. However, thesuccessful exercise of underlining the social and cultural aspects related to theself and the world around is vividly brought through these textbooks, and offersan appreciative way by its innovative and distinct approach to situate SocialSciences within the discourse of school knowledge.